2007
DOI: 10.1039/b703179c
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Li-ion transport in the garnet Li5La3Nb2O12

Abstract: We present a detailed study on the exact location and dynamics of Li ions in the garnet-type material Li(5)La(3)Nb(2)O(12) employing advanced solid state NMR strategies. Applying temperature-dependent (7)Li-NMR, (6)Li-MAS-NMR, (6)Li-{(7)Li}-CPMAS-NMR, (6)Li-{(7)Li}-CPMAS-REDOR-NMR as well as 2D-(6)Li-{(7)Li}-CPMAS-Exchange-NMR spectroscopy, we were able to quantify the distribution of the Li cations among the various possible sites within the garnet-type structure and to identify intrinsic details of Li migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
173
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(181 citation statements)
references
References 22 publications
7
173
1
Order By: Relevance
“…The mechanism involves immobile tetrahedrally coordinated Li sites (Wyckoff 24d) with the Li-ions hopping between the octahedral sites, bypassing these tetrahedral sites. 18,[21][22][23][24][25] Further experimental results corroborate the octahedral pathway mechanism with static Li cations on the tetrahedral sites. It was found that in Li 7 La 3 Zr 2 O 12 impurity ions like Al 3+ , which are necessary to stabilize the cubic garnet, are located on the tetrahedral 24d site.…”
Section: Introductionsupporting
confidence: 63%
“…The mechanism involves immobile tetrahedrally coordinated Li sites (Wyckoff 24d) with the Li-ions hopping between the octahedral sites, bypassing these tetrahedral sites. 18,[21][22][23][24][25] Further experimental results corroborate the octahedral pathway mechanism with static Li cations on the tetrahedral sites. It was found that in Li 7 La 3 Zr 2 O 12 impurity ions like Al 3+ , which are necessary to stabilize the cubic garnet, are located on the tetrahedral 24d site.…”
Section: Introductionsupporting
confidence: 63%
“…At room temperature the corresponding 6 Li NMR spin-lattice relaxation time is in the order of 1000 s whereas that of the main component is less than 10 s. Li 2 CO 3 might either stem from the preparation route chosen or from the reaction with ambient air as also found in the case of lithium lanthanum titanate (LLT) [20]. Note that the replacement of Li + by H + , which is the key reaction for the formation of Li 2 CO 3 in the case of LLT, was reported at least for the related garnet-type electrolytes Li 5 [21]. IR spectra in the mentioned work revealed the characteristic bands of carbonate ions.…”
Section: Al and 6 LI Mas Nmr Spectramentioning
confidence: 99%
“…In recent years, Li containing garnets have attracted large interest due to their potential usage as electrolytes in all-solid-state Li secondary batteries [1][2][3][4][5][6][7][8]. The high lithium-ion conductivity of such ceramics showing good electrochemical stability to lithium metal makes them promising candidates to be used, for example, in thin-film batteries [9].…”
Section: Introductionmentioning
confidence: 99%
“…This includes friends and colleagues both inside and outside SFB 458, as well as KF's past coworkers. To name just a few, in alphabetical order, we would especially like to thank A. Bunde Besides thanking our friends at SFB 458 for an atmosphere of intense engagement and healthy exchange of views, we also would like to cite a few relevant results of theirs [110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] which have added new insights while addressing issues complementary to those treated in this overview.…”
Section: Acknowledgementmentioning
confidence: 99%